2015
DOI: 10.1002/jssc.201500744
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective comprehensive two-dimensional gas chromatography. A route to elucidate the authenticity and origin ofRosa damascena Milleressential oils

Abstract: The analysis of Bulgarian and Turkish Rosa damascena Miller essential oils was performed by flow-modulated comprehensive two-dimensional gas chromatography using simultaneous detection of the second column effluent by flame ionization and quadrupole mass spectrometric detection. Enantioselective separations were obtained by running the samples on 2,3-di-O-ethyl-6-O-tert-butyldimethylsilyl-β-cyclodextrin column as the first column and on polyethylene glycol as the second column. The determination of enantiomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Retention data on 2,3‐di‐ O ‐Et‐6‐TBDMS‐β‐CD column published in for 14 lavender essential oil chiral markers and retention data we published recently on for GC×GC analysis for Rosa Damascena essential oil on the Rt‐βDEXse ( 1 D) + HP INNOWax ( 2 D) combination were used for identification purposes. Comparison of EI mass spectra obtained by FM‐GC×GC–qMS with spectra in the NIST/EPA/NIH MASS SPECTRALLIBRARY (NIST 14) was used as Supporting Information in identifying the components present in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retention data on 2,3‐di‐ O ‐Et‐6‐TBDMS‐β‐CD column published in for 14 lavender essential oil chiral markers and retention data we published recently on for GC×GC analysis for Rosa Damascena essential oil on the Rt‐βDEXse ( 1 D) + HP INNOWax ( 2 D) combination were used for identification purposes. Comparison of EI mass spectra obtained by FM‐GC×GC–qMS with spectra in the NIST/EPA/NIH MASS SPECTRALLIBRARY (NIST 14) was used as Supporting Information in identifying the components present in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The substances used for identification purposes were available in a reference stock solution at the Institute of Analytical Chemistry as already described in our recent paper .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, various compounds extracted from natural sources, such as fruits, vegetables, and plants, have been used for chemoprevention because they may have relatively lower toxicity as compared to their synthetic counterparts [ 1 , 2 , 3 , 4 ]. Farnesol is a constituent of essential oil derived from various plants such as citronella, lemon grass, tuberose, cyclamen, rose, neroli, balsam, and musk ( Table 1 ) ( Figure 1 ) [ 5 , 6 , 7 , 8 , 9 ]. It is a non-sterol isoprenoid (sesquiterpenoid alcohol) that can also be produced endogenously by the dephosphorylation of farnesyl pyrophosphate in the cholesterol biosynthesis pathway [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that ultra-high mass spectrometry (UHPLC/TOFMS) was used for the determination of botanical and geographical origins of Rosa damascena and detected adulterations. Krupcik et al (2015) applied enantioselective analysis of Bulgarian and Turkish Rosa damascena Miller essential oils for determination of their authenticity [39]. evaluated the effectiveness of Fourier transform infrared spectroscopy, Raman spectroscopy and gas-chromatography mass spectrometry combined with chemometrics for the determination of the authenticity of Rosa damascena essential oil.…”
Section: Discussionmentioning
confidence: 99%